The COLLECTIVE CREATIVE EFFICACY AS A MEDIATION OF THE INFLUENCE OF CREATIVE SELF EFFICACY ON STUDENTS' CREATIVITY: - - Erlina, Merly; Oktaviana, Mistety; Indrawati, Erdina; Diah Nurhadianti, RR. Dini (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
The purpose of this study was to investigate the mediating role of creative collective efficacy on the effect of creative self-efficacy on the creativity of a class X student team at SMAN 12 Tangerang Banten. The number of subjects who became the research sample was 122 people. The research method used is a quantitative method. The data analysis technique used by researchers is multiple analysis techniques and indirect effect analysis. The results of the study show that creative self-efficacy influences team creativity. Creative collective efficacy also influences team creativity. The results of the indirect effect analysis show that creative collective efficacy mediates the effect of creative self-efficacy on team creativity in class X students of SMAN 12 Tangerang Banten with a significance value of 0.00000124 <0.005.